The Acropora humilis group (scleractinia) of the Snellius expedition (1929-30) - van der Meij, S; Visser, R (Lee Kong Chian Natural History Museum, 2011)
During the Snellius expedition (1929-30) in eastern Indonesia and the Philippines, a large collection of Acropora corals was made. This collection is comprised of roughly 700 specimens, many of which remain unidentified. In this paper we discuss species of the Acropora humilis group collected during the expedition and compare the records with the known distribution ranges in Indonesia. New records are found, most notably for Acropora multiacuta, A. retusa and A. fastigata.